2014
DOI: 10.1111/eva.12188
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of genetic and phenotypic differentiation in two invasive salmonids in the southern hemisphere

Abstract: Invasion success may be expected to increase with residence time (i.e., time since first introduction) and secondary releases (i.e., those that follow the original introduction), but this has rarely been tested in natural fish populations. We compared genetic and phenotypic divergence in rainbow trout and brown trout in Chile and the Falkland Islands to test the prediction that adaptive divergence, measured as PST/FST, would increase with residence time and secondary releases. We also explored whether interspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 122 publications
(259 reference statements)
1
18
3
Order By: Relevance
“…However, the potential genetic impact of salmonids on galaxiids remains largely unknown (but see Vanhaecke et al, 2012a). Our estimates of relative salmonid abundance in Chilean streams were similar to those of previous studies that found salmonids were absent in some coastal rivers of Chilo e and were most abundant in areas with greater numbers of fish farms that could serve as sources for invaders (Young et al, 2010;Consuegra et al, 2011;Monz on-Arg€ uello et al, 2014b). We used two types of molecular markers with different rates of evolution and modes of inheritance to investigate the drivers of population structuring in A. zebra: maternally inherited mtDNA to provide information on historical phylogeographical events (e.g.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the potential genetic impact of salmonids on galaxiids remains largely unknown (but see Vanhaecke et al, 2012a). Our estimates of relative salmonid abundance in Chilean streams were similar to those of previous studies that found salmonids were absent in some coastal rivers of Chilo e and were most abundant in areas with greater numbers of fish farms that could serve as sources for invaders (Young et al, 2010;Consuegra et al, 2011;Monz on-Arg€ uello et al, 2014b). We used two types of molecular markers with different rates of evolution and modes of inheritance to investigate the drivers of population structuring in A. zebra: maternally inherited mtDNA to provide information on historical phylogeographical events (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…However, the potential genetic impact of salmonids on galaxiids remains largely unknown (but see Vanhaecke et al ., ). Our estimates of relative salmonid abundance in Chilean streams were similar to those of previous studies that found salmonids were absent in some coastal rivers of Chiloé and were most abundant in areas with greater numbers of fish farms that could serve as sources for invaders (Young et al ., ; Consuegra et al ., ; Monzón‐Argüello et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monzón‐Argüello, Consuegra, et al. () found that “secondary releases” (when referring to aquaculture escapes) have driven phenotypic divergence among naturalized rainbow trout from the Lake District in Chile. Recently, Bolstad et al.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic assessments have been instrumental in evaluating the geographic origin as well as drivers that explain the establishment and spread of naturalized rainbow trout in Patagonia (Gajardo, Díaz, & Crespo, ; Monzón‐Argüello, Garcia de Leaniz, Gajardo, & Consuegra, , ; Monzón‐Argüello, Consuegra, et al., ; Riva Rossi, Lessa, & Pascual, ). Recently, Benavente et al.…”
Section: Introductionmentioning
confidence: 99%